Antimicrobial resistance and genomic analysis of Vibrio parahaemolyticus isolates from foodborne outbreaks, Huzhou, China, 2019–2023 - Yan, Wei; Ji, Lei; Dong, Fenfen; Chen, Liping; Yuan, Rui; Zhang, Peng (Frontiers in Microbiology, 2024)
Objective The purpose of this study was to investigate the epidemiological and genomic characteristics of Vibrio parahaemolyticus (V. parahaemolyticus) isolates from outbreaks in Huzhou, China. Methods This study aims to analyze the epidemiological data on V. parahaemolyticus outbreaks reported in Huzhou from 2019 to 2023. A total of 70 V. parahaemolyticus outbreak isolates were collected. The antibiotic resistance, serotypes, molecular typing, and genomic characteristics of these isolates were analyzed. Results Most outbreaks of V. parahaemolyticus infection occurred in the summer, and the majority of outbreaks occurred in restaurants and rural banquets. High resistance rates were observed for ampicillin (AMP, 24.29%), followed by tetracycline (TET, 15.71%) and trimethoprim-sulfamethoxazole (SXT, 15.71%). The newly emerged serotype O10:K4 became dominant from 2021 to 2023, with most isolates belonging to ST3. The resistance gene blaCARB was frequently detected among these isolates. The pulsed-field gel electrophoresis (PFGE) and whole-genome single-nucleotide polymorphisms (wgSNPs) effectively differentiated the nine outbreaks. Conclusion The newly emerged serotype O10:K4 became dominant from 2021 to 2023, with most isolates being ST3. PFGE and WGS technologies provided reliable methods for typing and identifying V. parahaemolyticus for outbreaks.